The Miseno Lake (Central-Western Mediterranean Sea): An Overlooked Reservoir of Non-Indigenous and Cryptogenic Ascidians in a Marine Reserve - Virgili, Riccardo; Tanduo, Valentina; Katsanevakis, Stelios; Terlizzi, Francesco; Villani, Guido; Fontana, Angelo; Crocetta, Fabio (Frontiers in Marine Science, 2022)
Ascidians are the largest and most diverse class of the subphylum Tunicata, and are important components of marine benthic communities. They are also renowned worldwide invaders, of growing concern due to ease of spread and impacts on native biota. We hereby combined bathymetric and habitat mapping, extensive transect and photo-quadrat sampling, and a morphological and molecular study on selected specimens to evaluate taxonomic composition, cover, and distribution pattern of ascidians in a marine reserve of the central-western Mediterranean Sea, the Miseno Lake (Bacoli, Naples, Italy). Twenty-four taxa were found, of which 9 were non-indigenous species (NIS), 5 cryptogenic, and 10 native, delineating the Miseno Lake as a major hotspot of NIS and cryptogenic ascidians. DNA barcoding yielded 114 sequences, confirming identification for 22 taxa but also revealing single to few mismatches per species. Taxonomic insights were offered in the text and the Supplementary Material for several taxa, including the understudied Ascidia colleta and Ascidia malaca. The presence of a new clade was discovered in the Distaplia bermudensis species complex. Didemnum pseudovexillum and Polyclinum constellatum were respectively first recorded in Italy and western Mediterranean, and the same holds true for other taxa whose accurate identification was only possible through molecular evidence. The analysis of photographic archives allowed backdating and georeferencing to the Miseno Lake of the first records of Aplidium accarense and Botrylloides niger in Italy and of P. constellatum in the Mediterranean. Generalized Additive Models revealed that the abundance of NIS increased with availability of hard substrates (rocks or litter), decreased with depth, and was the highest in the channels connecting to other water bodies, followed by the peripheral areas of the lake. No certain evidence of competitive restriction of native ascidians was found. Finally, introduction pathways, potential impacts, and additional insights were discussed for NIS. The present study provides a baseline to evaluate shifts in the ascidian communities in the future, suggests that constant monitoring programs constitute crucial steps to achieve solid NIS management, and confirms marine reserves as widely vulnerable to biological invasions, especially when they coincide with potential hotspots of arrival or spreading such as semi-enclosed basins.